Landslide rainfall threshold for landslide warning in Northern Thailand - Avirut Chinkulkijniwat; Rattana Salee; Suksun Horpibulsuk; Arul Arulrajah; Menglim Hoy (Geomatics, Natural Hazards & Risk, 2022)
Northern Thailand is a hotspot for landslides. Rainfall-triggered landslides in this region have caused much suffering and many fatalities. In this work, a landslide-triggering rainfall threshold for Northern Thailand is proposed based on rainfall data relating to 48 triggering rainfall events that caused 59 landslides in the study area. To account for different mechanism of landslide formation, the threshold was portioned into two parts for different duration of rainfall events. A split point of 3 days was chosen as a separator for portioning the threshold to be 1) a threshold for rainfall events of duration no longer than 3 days and 2) a threshold for rainfall events of duration longer than 3 days. The threshold also required a suitable variable for antecedent rainfalls which was found to be cumulative rainfall over 25-day period (CR25) of 140 mm. Therefore, the thresholds combining cumulative rainfall with rainfall event - duration (CED) were established by incorporating the CR25 of 140 mm into the traditional ED threshold. This is the first attempt to incorporate the difference mechanism of landslide formation by dividing the CED threshold to two portions for difference rainfall duration. The introduced threshold shows positive sign of the prediction, particularly in term of false alarm rate, false alarm ratio, and critical success index. The introduced threshold will be useful for landslide warning system in the study area.